Self Regulation pada Remaja dalam Perspektif Islam (cara pandang dalam perspektif Psikologi dan Agama Islam menghadapi usia remaja dan problematikanya) - riyanda utari (LPPAIK Universitas Muhammadiyah Bandung, 2021)
The adolescent phase is a dynamic development stage where in this condition the demands of the environment require that adolescents can begin to prepare themselves to accept and carry out their responsibilities as adults but with inadequate physical, cognitive, social status conditions and are still in the transition phase of childhood. So, many interesting things happen in this phase. Including the brilliant achievements and deviations that occurred in this phase, and this is related to self-regulation. In psychology, the adolescent phase is a world where people are constantly looking for their identity, self-proof and the need for environmental recognition. In Islam, adolescence is the initial stage of a person to be able to determine the purpose of his life. Life experiences are used as a basis for practicing deciding, considering and processing information obtained in solving existing problems. Planning is an important asset in the lives of adolescents so that what they make of decisions has been the result of careful and directed consideration.